Body mass index associated with hyperglycemia and alterations of components of metabolic syndrome in Mexican adolescents Asociación entre índice de masa corporal, hiperglicemia y alteraciones de los componentes del síndrome metabólico en adolescentes mexicanos - Salvador Villalpando; Citlalli Carrión; Simón Barquera; Gustavo Olaiz-Fernández; Ricardo Robledo (Instituto Nacional de Salud Pública, 2007)
OBJECTIVE: This research aims to describe the epidemiology of obesity and its association with alterations in some components of metabolic syndrome, such as serum concentrations of glucose, insulin, and some lipids in a sub-sample of the Mexican Health Survey (MHS) of youth ages 10 to 19 years. MATERIAL AND METHODS: This analysis is based on a randomly selected sub-sample of the MHS of 20% of the youth ages 10 to19 years (n=1977), carried-out in Mexico in the year 2000 and distinguishes differences between national, rural and urban areas as well as four geographical country regions. Serum concentrations of glucose, insulin, triglycerides (TG), total cholesterol (TC) and HDL-cholesterol (HDLc) were measured. The protocol was approved by the Ethics Committee of the Mexican National Institute of Public Health. RESULTS: Overall, 14.8% of the individuals were overweight, 6.7% were obese and 37.5% had a family history of type 2 diabetes mellitus (DM2). The overall mean concentrations of glucose, insulin, total cholesterol, and triglycerides were significantly higher and those of HDLc were significantly lower in obese subjects than in individuals with normal Body Mass Index (BMI) (p< 0.05-0.001). The probability ratio (PR) of being in quintile 5 for glucose distribution was significantly higher for obese males and females (RP=2.1, p<0.001) than for their non-obese counterparts. It was also higher for females with a history of DM2 (RP=1.12, p<0.02), but not for males. The PR of being in quintile 5 for insulin distribution was significantly higher for obese males (RP=3.51, p<0.001) and females (RP=3.3, p<0.001) than for non-obese counterparts. It was also higher for male (RP=1.28, p<0.02) and female (RP=1.27, p<0.02) subjects with a history of DM2. Finally, the PR for being in quintile 5 for TG distribution was significantly higher for obese males (RP=4.71, p<0.001) and females (RP=1.75, p<0.001) than for their non-obese counterparts. DISCUSSION: A strong association between obesity and the risk of higher concentrations of glucose, insulin, TG, and TC and a lower concentration of HDLc in youth has been demonstrated. These findings stress the risk of obesity at these early ages, with alterations in some of the components of metabolic syndrome. OBJETIVO: Esta investigación tiene como objetivo describir la epidemiología de la obesidad y de su asociación con alteraciones de algunos componentes del síndrome metabólico, tales como las concentraciones séricas de glucosa, insulina y algunos lípidos en una muestra de jóvenes con edades entre 10-19 años estudiados en la Encuesta Nacional de Salud (ENSA). MATERIAL Y MÉTODOS: El presente análisis está basado en una submuestra de 20% de los sujetos de la ENSA, realizada en México en el año 2000, con edades entre 10-19 años (n=1977) seleccionada aleatoriamente, con poder para distinguir diferencias a nivel nacional, urbano rural y por cuatro regiones geográficas del país. Se midieron en el suero las concentraciones de glucosa, insulina, colesterol total (CT), triglicéridos (TG) y colesterol-HDL (cHDL). El protocolo fue aprobado por el Comité de Ética del Instituto Nacional de Salud Pública. RESULTADOS: El 14.8% de la muestra tuvieron sobrepeso, 6.7% obesidad y 37.5% tenían una historia familiar de diabetes mellitus tipo2 (DM2). La media de las concentraciones de glucosa, insulina, CT y TG fueron significativamente mayores y los de cHDL significativamente menores en los sujetos obesos que en los que tenían índice de Masa Corporal (IMC) normal (p<0.05-0.001). La razón de probabilidades (RP) de estar en el quintil 5 de la distribución de glucosa fue significativamente mayor para los hombres y mujeres con obesidad (RP=2.1, p<0.001) que para sus contrapartes no obesos, para la mujeres con historia familiar de DM2 (1.12, p<0.02), pero no para los hombres. La RP de estar en el quintil 5 de la distribución de insulina fue mayor para los hombres (RP=3.51, p<0.001) y para las mujeres (RP=3.3, p<0.001) con obesidad que para aquellos con IMC normal, así como para los hombres (RP=1.28, p<0.02) y las mujeres (RP=1.27, p<0.02) con historia familiar de DM2. La RP de estar en el quintil 5 de la distribución de triglicéridos fue mayor en los hombres (RP=4.71, p<0.001) y las mujeres (RP=1.75, p<0.001) obesos que en los no obesos. CONCLUSIONES: Se observó una fuerte asociación entre la obesidad y el riesgo de tener altas concentraciones de glucosa, insulina, TG y CT y bajas de cHDL en jóvenes. Tales hallazgos confirman el riesgo que tiene la obesidad de asociarse con anormalidades de algunos componentes del síndrome metabólico en jóvenes.